PERBANDINGAN INDIKATOR KINERJA KEUANGAN PEMERINTAH PROVINSI DI INDONESIA - Marissa Magdalena; Ch Heni Kurniawan (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2013)
The aim of this study was to compare the fnancial performance indicators in Indonesian Provincial Government, Provincial knowing who has the best performance, and to determine whether there are diferences in the Indonesian province of fnancial performance based on indicators of independence, efectiveness, and harmony in 33 provinces in Indonesia . The data used in this study is a secondary data ie the budget statements and budget realization report from 33 provinces in Indonesia in 2010. The data is taken from (www.djpk.depkeu.go.id) and the Provincial Government Finance Statistics 2008-2011 which is a catalog of the BPS. The analysis technique used in this study is the analysis of the fnancial performance of the independence of the Provincial Government, the Provincial Government of the efectiveness of the fnancial performance, fnancial performance and compatibility with the provincial government public service expenditure ratio. To test the hypothesis, test diferent statistical instruments used are Kolmogorov Smirnov test with a signifcance level of 0.05. Te analysis showed that the provincial government ‘s fnancial performance has ranked the best performance is the province of Banten. Te results of the analysis indicate that the independence of East Java Province has the highest rank is 74.93 % and West Papua has the lowest rating that is 3.69 %. Te results of the analysis indicate that the efectiveness of the province of West Papua has the highest rank 167.21 % and Central Kalimantan province has the lowest rank is 71.10 %. Te results of the analysis showed that the harmony of Central Java province have the ofcers expenditure ratio is 90.92 % and the highest value of the ratio of expenditure on public services Riau Province has the highest rank is 46.03 %. While the diferent test results demonstrate the value of Kolmogorov Smirnov sig asym three fnancial indicators have a value > 0.05 is 0.933, this means that there is no signifcant diference in the fnancial performance of the Provincial Government of Indonesia.